Eleven minutes - Coelho, Paulo; Costa, Margaret Jull (New York : Perennial, 2005)
Embittered by her first experiences of love, a young Brazilian girl travels to Geneva in search of fame and fortune and finds her beliefs about sex and romance challenged by her relationship with a young painter.
"First published in Brazil in 2003 as Onze Minutos by Editora Rocco. A hardcover edition of this book was published in 2004 by HarperCollins Publishers."--Title page verso.
"P.S. insights, interviews & more--"--Cover.
Keywords: Prostitutes -- Brazil -- Fiction; Brazilians -- Switzerland -- Geneva -- Fiction